Prevalence, Trends, and Harm Perception Associated with E-Cigarettes and Vaping among Adolescents in Saudi Arabia - Rayes, Bayan T; Alalwan, Abdulaziz; AbuDujain, Nasser M; Darraj, Ali; Alammar, Muath A; Jradi, Hoda (Archives of Clinical and Biomedical Research, 2023)
Introduction: Younger generations are an important market for the tobacco products industry since most smokers try their first cigarette before the age of 18. Electronic cigarettes (e-cigarettes) are a common mode of smoking among teens, and the number of users is increasing exponentially. Objective: This study aimed to estimate the current prevalence of e-cigarettes and vaping usage among adolescents between the ages of 15 and 19 in the city of Mecca, Saudi Arabia. Methods: This study was conducted among 534 students at four high schools. They were asked to complete a 23-item questionnaire retrieved from the Global Youth Tobacco Survey. Descriptive statistics and regression analysis were conducted. The study was approved by the Ministry of Health Saudi Arabia Medical Research Center Institutional Review Board committee on October 10, 2018 (research number 18-506E). Results: A total of 109 (20.6%) of the participants reported being smokers of e-cigarettes. Being a male (OR = 1.55; 95% CI: [1.01–2.37]), in the second year of high school (OR = 2.91; 95% CI: [1.61–5.24], ever experimenting with regular tobacco cigarettes, being a current shisha smoker, living with a smoker, and believing that e-cigarettes are less addictive than traditional cigarettes are all factors independently associated with e-cigarette use in this sample of adolescents. Conclusion: Among adolescent smokers, even minimal experience with smoking is correlated with pro-smoking attitudes. E-cigarette use is common in adolescents and related to the use of other combustible tobacco products. Tobacco control efforts at all levels should eliminate factors fostering future tobacco use to minimize the burden of disease and disability in